Visual Identity Redesign of the Gelora Bung Karno Complex - Lim, Natashia; Melini, Ellis; Zulkarnain, Alfiansyah; Suwanto , Kartika Magdalena (Universitas Multimedia Nusantara, 2025)
The Gelora Bung Karno (GBK) Complex is a national heritage site in Indonesia. It has changed from a sports facility into a public space that is open, inclusive, and multifunctional. This transformation requires rebranding to reflect its new role while keeping its historical and national spirit. Visual identity plays an important role in this process. It is not just about how things look, but how people see and understand the place. Based on Alina Wheeler’s idea, visual identity is a planned way to shape public perception and build loyalty. The new identity for GBK is based on two things: its well-known architecture that’s reflected in the logo, and cultural motifs from across Indonesia. These ideas helped create a new logo, a color system for various applications, and graphic patterns inspired by local textiles. The research methods used include benchmarking other public spaces, interviews with users and staff, and visual studies of the landmark inside the complex. These helped guide the design process and make sure the results were meaningful and useful. This paper explains the process of research & analysis phase, clarifying strategy, up to the design stage and the resulting visual identity system. Keywords: gelora bung karno; complex; visual identity; national heritage; Indonesia; rebranding